2014
DOI: 10.1002/acp.2998
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Working Memory when ‘Learning How’ with Multimedia Learning Material

Abstract: SummaryThe aim of the reported experiment was to obtain insight into how learners' visuo‐spatial working memory is involved during learning how to perform procedural‐motor tasks from a multimedia instruction (i.e. ‘learning how’). Eighty‐two participants studied first‐aid procedures using text only or multimedia. Working memory involvement was gauged by measuring the interference between learning first‐aid procedures and performing a spatial dual task. Learning outcomes were measured as task performance and ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 60 publications
3
16
0
Order By: Relevance
“…For assembly, similar results were obtained with multimedia and picture‐only instructions. In sum, research about the effects of format of instructions on memory and assembly performance is scarce and has found an advantage of multimedia presentations (Brunyé et al, , 2007; Michas & Berry, ; Novick & Morse, ; van Genuchten et al, ; Zacks & Tversky, ), or similar results with multimedia and picture‐only presentations (Brunyé et al, ).…”
Section: Multimedia Effect In Procedural Textmentioning
confidence: 99%
See 4 more Smart Citations
“…For assembly, similar results were obtained with multimedia and picture‐only instructions. In sum, research about the effects of format of instructions on memory and assembly performance is scarce and has found an advantage of multimedia presentations (Brunyé et al, , 2007; Michas & Berry, ; Novick & Morse, ; van Genuchten et al, ; Zacks & Tversky, ), or similar results with multimedia and picture‐only presentations (Brunyé et al, ).…”
Section: Multimedia Effect In Procedural Textmentioning
confidence: 99%
“…Studies addressing the multimedia effect in procedural texts have also found an overall benefit for the multimedia conditions (text and pictures), in comparison with text‐only conditions (Brunyé et al, ; Marcus, Cooper, & Sweller, ; Michas & Berry, ; Mills et al, ; Novick & Morse, ; van Genuchten, van Hooijdonk, Schüler, & Scheiter, ; Zacks & Tversky, ). For example, Brunyé et al () examined the association between format of instruction presentation and memory, and found better recall of instructions in the multimedia condition.…”
Section: Multimedia Effect In Procedural Textmentioning
confidence: 99%
See 3 more Smart Citations